Chinese Medicine, Succinum, Ameliorates Cognitive Impairment of Carotid Artery Ligation Rats and Inhibits Apoptosis of HT22 Hippocampal Cells via Regulation of the GSK3β/β-Catenin Pathway - Wei, Chongqi; Zhu, Ziqiang; Zheng, Jia-ni; Lu, Yunqing; Cao, Cheng; Qu, Suchen; Liu, Mengqiu; Meng, Xue-er; Lou, Qianyin; Wang, Qingqing; Duan, Jin-ao; Shang, Er-xin; et al. (Frontiers in Pharmacology, 2022)
Succinum is an organic mineral formed from the resin of ancient coniferous and leguminous plants, which is applied for tranquilizing mood, promoting blood circulation, and removing blood stasis in Chinese medicine. For quite a long time, the modern research of succinum mainly focuses on the study of physical and chemical properties and authenticity identification while few reports on its medicinal mechanism. In current study, we evaluated different solvent extracts of succinum on carotid artery ligation rats mimicking vascular dementia. It was found that ethyl acetate extracts of succinum significantly improved the learning and memory abilities of model rats and inhibited neuronal apoptosis in the hippocampus. On a mice hippocampal neuronal cell line (HT22), ethyl acetate extracts of succinum also exerted better action trend in inhibiting cell apoptosis induced by oxygen glucose deprivation (OGD). By using XAV-939 on both in vivo and in vitro studies, it was found that ethyl acetate extracts of succinum might exert these functions by regulating the GSK3β/β-catenin pathway. These studies revealed the neuronal function of succinum, which explained the traditional effects of succinum and provided more modern scientific basis for its clinical application.